Very large scale integration architectures of discrete transforms for digital signal processing applications - Wang, Chao (2010)
Many discrete transforms, such as the fast Fourier transform (FFT), critical-band transform (CBT), and discrete wavelet packet transform (DWPT), have been successfully used in a wide range of digital signal processing (DSP) applications. However, these discrete transform algorithms are always computational and memory intensive, which may result in a performance bottleneck, increase hardware implementation cost, or lead to significant power consumption.